The minimal length case of the Klein Gordon equation with hyperbolic cotangent potential using Nikivorof-Uvarof Method - Isnaini Lilis Elviyanti; Ahmad Aftah Syukron (Universitas Sebelas Maret, 2020)
The case of minimal length is applied for the Klein Gordon equation with hyperbolic cotangent potential. The Klein Gordon equation for minimal length case is solved used to approximate solution. The energy eigenvalue and wave function are investigated by the Nikivorof-Uvarof method.